2019
DOI: 10.3390/ijms20143607
|View full text |Cite
|
Sign up to set email alerts
|

Infusing Mesenchymal Stromal Cells into Porcine Kidneys during Normothermic Machine Perfusion: Intact MSCs Can Be Traced and Localised to Glomeruli

Abstract: Normothermic machine perfusion (NMP) of kidneys offers the opportunity to perform active interventions, such as the addition of mesenchymal stromal cells (MSCs), to an isolated organ prior to transplantation. The purpose of this study was to determine whether administering MSCs to kidneys during NMP is feasible, what the effect of NMP is on MSCs and whether intact MSCs are retained in the kidney and to which structures they home. Viable porcine kidneys were obtained from a slaughterhouse. Kidneys were machine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 32 publications
3
47
0
Order By: Relevance
“…This may be mirrored in our NMP model -MAPC cells are homing to hypoxic areas within a marginal kidney where they take temporary residence. In this environment, the cells release an anti-inflammatory secretome which is having beneficial effects, resulting in The findings of this study reflect similar work investigating pig kidneys treated with human mesenchymal stromal cells (MSC) during NMP 40,41 . These studies have similarly demonstrated tracked cells mainly localising to the glomeruli.…”
Section: Determining the Physical Distribution Of Nmp Administered Masupporting
confidence: 77%
“…This may be mirrored in our NMP model -MAPC cells are homing to hypoxic areas within a marginal kidney where they take temporary residence. In this environment, the cells release an anti-inflammatory secretome which is having beneficial effects, resulting in The findings of this study reflect similar work investigating pig kidneys treated with human mesenchymal stromal cells (MSC) during NMP 40,41 . These studies have similarly demonstrated tracked cells mainly localising to the glomeruli.…”
Section: Determining the Physical Distribution Of Nmp Administered Masupporting
confidence: 77%
“…In addition, targeted delivery of MSC to the injured organ would be useful to improve their interplay with the injured tissue. Direct infusion through the renal artery and delivery during normothermic machine perfusion are plausible options to deliver cells specifically to the kidney and ensure MSC interaction with damaged renal endothelium during organ preservation [24].…”
Section: Discussionmentioning
confidence: 99%
“…A better understanding of these interactions will enable us to optimize the potential regenerative effect of MSC therapy on endothelial injury. The first data about MSC delivery to the kidney during ex situ normothermic machine perfusion show a distribution of MSC to the renal microvasculature, with MSC localizing to the renal cortex [24]. Although data suggest that MSC may possess renal regenerating effects after administration to the kidney [25], it is unknown whether this involves endothelial repair, and if so which mechanisms are involved.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, targeted delivery of MSC to the injured organ would be useful to improve their interplay with the injured tissue. Direct infusion through the renal artery or delivery during normothermic machine perfusion are plausible options to deliver cells speci cally to the kidney and ensure MSC interaction with damaged renal endothelium during the organ preservation (24).…”
Section: Discussionmentioning
confidence: 99%
“…A better understanding of these interactions will enable us to optimize the potential regenerative effect of MSC therapy on endothelial injury. The rst data about MSC delivery to the kidney during ex situ normothermic machine perfusion show a distribution of MSC to the renal microvasculature, with MSC localizing to the renal cortex (24). Although data suggest that MSC may possess renal regenerating effects after administration to the kidney (25), it is unknown whether this involves endothelial repair, and if so which mechanisms are involved.…”
Section: Introductionmentioning
confidence: 99%